JONATHAN EDWARDS AND THE LIFE OF GOD: TOWARD AN EVANGELICAL THEOLOGY OF PARTICIPATION - Minkema, Kenneth P. (Jonathan Edwards studies, 2015)
Hastings, W. Ross. Jonathan Edwards and the Life of God: Toward an Evangelical Theology of Participation. Minneapolis: Fortress Press, 2015. Pp. xvi, 524. ca. US $ 46.